Real Lives in the Sixteenth Century - Ard Boone, Rebecca, author.
1 online resource
Keywords: "Real Lives in the Sixteenth Century presents a global history using four sets of biographies to illustrate similar situations in different geographical regions. The vibrant narratives span four continents and include the following pairs: Henry IV of France and Hideyoshi of Japan, Hèurrem Sultan (Roxelana) of the Ottoman Empire and Lady Zheng of the Ming Dynasty, Afonso I of Kongo and Elizabeth I of England, and Pope Clement VII and Moctezuma II of Mexico.Through exploring the lives of eight individuals from a variety of cultural settings, this book encourages students to think about the big questions surrounding human interactions and the dynamics of power. It introduces them to a number of key historical concepts such as feudalism, dynasticism, religious syncretism and slavery, and is a springboard into history of the wider world, blending together aspects of political, cultural, intellectual and material history. Accessibly written and containing timelines, genealogical tables and a number of illustrations for each biography, Real Lives in the Sixteenth Century is the ideal introductory text for undergraduates of pre-modern World History and of the sixteenth century in particular. "--Provided by publisher.